FACTORS INFLUENCING THE USE AND NON-USE OF CRASH HELMET BY TERTIARY EDUCATION STUDENTS IN THE WA MUNICIPALITY, GHANA - Musah, H.; Marfo, S.; Akpade, J. (UDS International Journal of Development, 2019)
The motorcycle has become a preferable means of transport in Ghana due to its cost effectiveness and convenience. Apparently, motorcycle use involves a number of risks such as head injuries and deaths due to non-use or improper use of crash helmets. Against this background, an explorative case study design was conducted with the objective of ascertaining the factors that influence the use and non-use of helmets among student motorcyclists. Quota sampling technique was used in selecting 90 student motorcyclists from the University for Development Studies- Wa Campus, Wa Polytechnic and University of Education, Winneba-Wa Center. In addition, 11 key informants were purposely selected. Primary data was gathered through interviews. The study found that; traveling distance, discomfort and the type of ‘hair- do’ were some of the major factors accounting for the non- use of helmets. The study also revealed that protection of the head against danger and the eyes against foreign materials are the main motivating factors for the use of crash helmets. This study recommends that the Police Motor Traffic and Transport Department, the National Road Safety Commission, the Management and Student Leadership of Tertiary Institutions, the Health Ministry, the Media and Drivers and Vehicle License Authority should develop holistic education and enforcement measures to prevent the non-use of crash helmets among student motorcyclists. Keywords: Crash Helmet, Tertiary Students, Motorcycle, Wa, Ghana